Web System Dedicated to Parallel Computation for Modeling of Mushy Steel Deformation - Dębiński T.; Głowacki M.; Hojny M.; Gumuła A.; Woźniak D. (Archives of Metallurgy and Materials, 2014)
The paper presents web base system for an application of parallel object-oriented programming technique in modelling of rolling process of steel plates with semi-solid zone. It also throws light on the problem of semi-solid steels yield stress relationship, one of the main input data of the simulation, and on application of inverse solution, the only possible method of development of the stress-strain curves at extremely high temperatures. Due to limitations of available computer resources a very accurate computation can sometimes be impossible or the time performance can be a barrier for practical application of complex sequential models. Taking advantage of parallel computing the authors have developed an algorithm allowing for fast computation using multiple processors, which is the main subject of the presented paper.